2020
DOI: 10.1002/ajpa.23993
|View full text |Cite
|
Sign up to set email alerts
|

Commingled crypts: Comparative health among Byzantine monastics in the Levant

Abstract: Objectives: Early Byzantine (A.D. 330-842) monastic rules stipulated that entrants relinquished familial connections, personal belongings and secular relationships to become part of the ascetic collective that continued in death, resulting in bioarchaeological marginalization, as was the case of the monastics excavated from the Chapel of Robebus at Mount Nebo, Jordan (ca. A.D. 491-640). It was hypothesized that compared to contemporary monastic groups, the Mount Nebo monastics experienced poorer health and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…
Commingling of human skeletal remains, where bones from more than one person are mixed up in an assemblage, has been a complex issue in the field of forensic anthropology for decades. Commingling can occur in a variety of circumstances, such as natural disasters, airplane crashes, terrorist attacks, and wars or conflicts [1][2][3][4][5][6][7][8].Commingled remains obstruct the personal identification process because the estimation of biological characteristics relies on combined data from multiple points of the skeleton [9]. Further, if some of the remains cannot be associated with an individual, then it is unlikely that those elements will be returned to the decedent's family for final deposition.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Commingling of human skeletal remains, where bones from more than one person are mixed up in an assemblage, has been a complex issue in the field of forensic anthropology for decades. Commingling can occur in a variety of circumstances, such as natural disasters, airplane crashes, terrorist attacks, and wars or conflicts [1][2][3][4][5][6][7][8].Commingled remains obstruct the personal identification process because the estimation of biological characteristics relies on combined data from multiple points of the skeleton [9]. Further, if some of the remains cannot be associated with an individual, then it is unlikely that those elements will be returned to the decedent's family for final deposition.
…”
mentioning
confidence: 99%
“…Commingling of human skeletal remains, where bones from more than one person are mixed up in an assemblage, has been a complex issue in the field of forensic anthropology for decades. Commingling can occur in a variety of circumstances, such as natural disasters, airplane crashes, terrorist attacks, and wars or conflicts [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Religious people were also deeply involved in the economic and social history. Human remains from convents and cathedrals, being important osteological and anthropological records, are also predominantly used in studies to address differences between ecclesiastical and lay people (e.g., DeWitte et al, 2013;Mays, 1997;Müldner & Richards, 2007;Quintelier et al, 2014), diseases (e.g., Judd, 2020;Rogers & Waldron, 2001;Väre et al, 2020), or diet and mobility (e.g., Ahlin Sundman, 2018;Müldner et al, 2009;Sarkic et al, 2019).…”
mentioning
confidence: 99%
“…In addition, the commingled nature of remains may render the calculation and interpretation of disease prevalence challenging (Perry and Edwards 2021). Despite these many limitations, recent paleopathological studies in Europe and the Middle East have demonstrated the possibilities of differential diagnoses of these challenging commingled contexts (e.g., Abegg et al 2021;Assis et al 2018;Austin 2017;Brickley and Buckberry, 2015;Judd 2019;Perry and Edwards 2021). Perry and Edwards (2021) advocate for the use of the biological approach when carrying out differential diagnoses of skeletal lesions which examines each lesion independently and "identifies the underlying biological processes that could produce the skeletal lesions observed" (Perry and Edwards 2021:222), explaining that such an approach is preferred by many paleopathologists as it "allow recognition of co-or multimorbid conditions, rather than assuming all observations present a suite of skeletal lesions from one condition" (Perry and Edwards 2021:222).…”
Section: Challenges and Recent Developmentsmentioning
confidence: 99%